The Lepage Experience - Boantă, Adriana (Theatrical Research, 2022)
Our study reflects Lepage’s central contribution to contemporary performance practices by creating complex theatrical productions with a strong visual impact that combines with new technologies and multimedia techniques, completely reinventing the theatrical space.